1973
DOI: 10.1111/j.1365-2672.1973.tb04101.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spectinomycin Resistance as a Marker for Ecological Studies with Rhizobium spp.

Abstract: ABSTRACT. Resistance to the antibiotic spectinomycin has been examined as a possible marker to supplement streptomycin resistance in ecological or genetic studies with rhizobia. Single step spontaneous mutants resistant to high levels of spectinomycin were isolated from 8 effective strains representing 4 species of Rhizobium. There was no evidence of cross resistance to streptomycin, and streptomycin resistant mutants were not cross resistant to spectinomycin. Minor changes in antigenic characteristics examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…trifolii A TCC 14480 were kindly supplied by the late Prof. Maruyama (The University of Tokyo) and Dr. Garno (Institute of Agrobiological Resources), respectively. Rhizobium fredii USDAI91 Kas r , USDAI92 Kas r , and USDAI93 Kas r , which are resistant to 1,000 mg L -1 kasugamycin, were derived from the parent strains USDAI91, USDAI92, and USDAI93 by the method of Schwinghamer and Dudman (1973). E. coli HB101 and K802 were grown in TY (Beringer 1974) medium.…”
Section: Methodsmentioning
confidence: 99%
“…trifolii A TCC 14480 were kindly supplied by the late Prof. Maruyama (The University of Tokyo) and Dr. Garno (Institute of Agrobiological Resources), respectively. Rhizobium fredii USDAI91 Kas r , USDAI92 Kas r , and USDAI93 Kas r , which are resistant to 1,000 mg L -1 kasugamycin, were derived from the parent strains USDAI91, USDAI92, and USDAI93 by the method of Schwinghamer and Dudman (1973). E. coli HB101 and K802 were grown in TY (Beringer 1974) medium.…”
Section: Methodsmentioning
confidence: 99%
“…Resistance of a rhizobial strain to a particular antibiotic is a useful marker (Schwinghamer and Dudman, 1973;Pankhurst, 1977;Beynon and Josey, 1980;Turco et al, 1986). It is important that antibiotic-resistant strains that are selected for inoculation experiments have not lost their infectiveness (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Antoun (1982) questioned the reliability of genetically marked, resistant mutants for symbiotic properties when used to study rhizobial ecology. Schwinghamer and Dudman (1973) reported no change in the Ngfixation effectiveness of antibiotic-resistant mutants of…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Antibiotic resistance is one method that enables the recovery of the introduced strain from a sterile or non-sterile environment. The use of bacterial strains resistant to high levels of antibiotics to study rhizobial ecology was demonstrated by Danso et al (1973), Dudman (1973), andPankhurst (1977).…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation